2022
DOI: 10.3389/fpsyg.2022.804313
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Helping EFL Students Improve Their Writing Through Written Feedback: The Case of Native and Non-native English-Speaking Teachers' Beliefs

Abstract: Although the efficacy of teacher written feedback has been widely investigated, relatively few studies have been conducted from feedback practitioners' perspectives to investigate teachers' beliefs regarding it, particularly compare beliefs held by teachers with different sociocultural and linguistic backgrounds. Consequently, much remains to be known about teachers' conceptions about written feedback, who has different first languages (L1). To bridge such a gap, we conducted this qualitative study to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 102 publications
(174 reference statements)
0
16
0
Order By: Relevance
“…This finding negates that of Cuban (2005) who asserts that lecturers had a negative perception and were resistant to the use of educational technology. In recent times, there has been an increased clamour for the adoption of technology in teaching-learning concerns (Cheng and Zhang, 2022; Vinagre and Muñoz, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding negates that of Cuban (2005) who asserts that lecturers had a negative perception and were resistant to the use of educational technology. In recent times, there has been an increased clamour for the adoption of technology in teaching-learning concerns (Cheng and Zhang, 2022; Vinagre and Muñoz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It can be implemented synchronously (during class) or asynchronously (after class) (Bahari, 2021) while boosting students' writing skills (Adrefiza and Fortunasari, 2020; Hanan et al ., 2022). Feedback reforms lecturers' supervision competence and students’ learning (Algiraigri, 2014; Cheng and Zhang, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, the term “alignment” indicates teachers’ instructional processes, intended outcomes, and assessments in accordance with students’ demands and interests. In contrast, misalignments between teachers and students can cause problems such as students feeling frustrated that teachers fail to meet their needs and affect students’ learning outcomes and their evaluations of teachers ( Rao, 2010 ; Yang, 2018 ; Cheng and Zhang, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, research has shown that NESTs’ views of effective teaching are often viewed as misaligned with local Chinese EFL teachers and students. For example, NESTs’ teaching styles conflicted with Chinese EFL students’ learning styles, and their preferences for writing feedback differed from local Chinese teachers ( Rao, 2010 ; Cheng and Zhang, 2022 ). These findings indicate that NESTs in China have introduced teaching methods that might have succeeded in other settings but have not adapted their teaching to the students’ cultural and linguistic contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation